Helminthosporium paraoligosporum sp. nov., a new ascomycetous fungus from Ontario, Canada - Ilyukhin, Evgeny; Markovskaja, Svetlana (Phytotaxa, 2023)
A novel anamorphic ascomycetous fungus, Helminthosporium paraoligosporum (Pleosporales, Ascomycota), isolated from branches of linden trees is described and characterized. The species is morphologically distinct from other Helminthosporium spp. by shorter conidiophores and conidia, and culture characteristics. Phylogenetic analysis of a combined set of ITS and LSU sequence data also supports the establishment of a new species. H. paraoligosporum is clustered with H. caespitosum, H. oligosporum, and H. tiliae. The species in this clade have similar morphological characteristics and host affiliation. In particular, conidiophores of the species (except H. tiliae) can be reduced to elongated conidiogenous cells. H. caespitosum is associated with Betula spp., while the other species in this clade have been collected from Tilia spp. only.